Emergence of Ecotourism in Thailand - Trivedi , Akhilesh; Boonparkob, Yanapa; Kachendecha, Cheewin; Pitirote , Sasiphatr (Dusit Thani College Journal, 2020)
The purpose of this paper is to study ecotourism in Thailand. Ecotourism is tourism in a natural environment where tourism resources are well-taken care, and also tourists can learn and enjoy nature; while local community take part in the management of ecotourism. The sustainable growth of the foreign tourist arrivals is encouraging Thailand to promote the ecotourism to provide a wider scope of it. The ecotourism plays a major role to eradicate poverty of isolated part of the underdeveloped areas of the nation. Therefore, the needs of drastic ecotourism policies to promote and designate areas for ecotourism destinations. The role of the government organization is identifying the new eco-destination and develop basic infrastructure for it. Finally, after reviewing various literature can be concluded with guidelines for eco-tourism and its needs for long-term strategic government policies to maintain the ecosystem in Thailand.